AtCRY2 Negatively Regulates the Functions of AtANN2 and AtANN3 in Drought Tolerance by Affecting Their Subcellular Localization and Transmembrane Ca2+ Flow - Liu, Ting; Du, Leyan; Li, Qiushi; Kang, Jingda; Guo, Qi; Wang, Shilin (Frontiers in Plant Science, 2021)
Annexins are a multifunctional class of calcium-binding proteins in plants, and their physiological functions and regulation in response to drought stress remain to be elucidated. Here, we found that AtANN2 and AtANN3 conferred to drought tolerance under short-day and long-day conditions, respectively. Under their functional photoperiod, AtANN2 and AtANN3 gene expression was enhanced in the mannitol-treated roots, and their encoded proteins were rapidly targeted to the plasma membrane, and mediated significant Ca2+ flows across the plasma membrane. Cryptochromes as photoreceptors can not only sense the photoperiod and regulate ion channels on the plasma membrane to influence ion flow but also induce downstream physiological responses. AtCRY2 repressed the functions of AtANN2 and AtANN3 by affecting their plasma membrane localization and inhibited AtANN2- and AtANN3-dependent transmembrane Ca2+ flow in response to drought stress. Taken together, these results uncover a mechanism linking Annexins-AtCRY2 to transmembrane Ca2+ flow and resulting in enhanced drought tolerance in Arabidopsis.